THE STRENGTHENING MSMEs WITH AGRICULTURAL PRODUCTS AND PROCESSED PRODUCT THROUGH THE EMPOWERMENT OF HOUSEWIFE DURING THE COVID-19 PANDEMIC - Jajuk Herawati; Dwie Retna S.; Diah Tri Hermawati; Ernawati Ernawati; Sophie Tita H. (International Journal of Engagement and Empowerment, 2022)
Community Service Program (PkM) in Petiken Village Driyorejo District, Gresik Regency East Java province, aims to grow and improve the ability of homemakers to process agricultural products to earn income to enhance welfare through active involvement, both initiative and participatory. This activity will be carried out using the PRRA (Participatory Rapid Rural Appraisal) and RRA (Rapid and Rural Appraisal) methods among homemakers and the Faculty of Agriculture Assistant - UWKS and students. With this PkM proposal, FP - UWKS, as one of the universities in Indonesia, especially East Java, which carries out activities, can contribute to efforts to improve community welfare by empowering homemakers. This PkM is important to be proposed and carried out to support accelerating the achievement targets of the UWKS College Strategic Plan, where the UWKS Main Research and Service Umbrella is following the Rector's Decree in 2012. The umbrella for superior research and service for the LPPM-UWKS institution is " Scientific and Environmental Insight ", where this institution's flagship umbrella is a basic reference for lecturers to develop self-reliance and creativity in arranging service activities at UWKS